Modeling and simulation of solids oxide fuel cell based distributed generation system - Mohideen Safiee b Ibrahim (2023)
Although huge advances in solid oxide energy component (SOFC) innovation have been made, one impediment must be tended to before their benefits can be completely figured it out.